Impact of Acacia arabica Addition on Optical, Mechanical, and Fungicidal Properties of Polymethyl Methacrylate Denture Base Material - Moussa, Rania; Alqutaibi, Ahmed Yaseen; Zafar, Muhammad Sohail; El-Din, Mai Salah (European Journal of Dentistry, 2025)
The aim of the study was to evaluate the optical, mechanical, and microbiological performance of heat-cured polymethyl methacrylate (PMMA) modified by adding various gum Acacia arabica (GA) concentrations.Specimens containing 1, 2.5, 5, 7.5, and 10% GA by weight were prepared, with control specimens containing no GA. Thirty-six rectangular samplings were assessed for color changes, flexural strength, and elastic modulus. Color measurement was conducted using a spectrophotometer. A universal testing machine measured flexural strength through a three-point bending test, and the elastic modulus was calculated. A profilometer and Vickers hardness tester evaluated the surface roughness and hardness. Antifungal activity was assessed by incubating specimens with Candida albicans and counting colony-forming units (CFU/mL).Data were analyzed using the Kruskal-Wallis test for antifungal activity and optical properties and One-way ANOVA for mechanical properties at a significance level of p < 0.05.Groups with higher GA concentrations exhibited significant color changes (p < 0.001). Nonsignificant changes were reported in flexural strength, elastic modulus, or surface hardness (p >0.05), although lower concentrations of GA (1 and 2.5% wt) improved surface hardness. Both 7.5% and 10% wt GA significantly increased surface roughness (p < 0.001). Antifungal activity increased with GA concentration declining from 12 × 108 CFU/mL in the control to no detectable fungal growth in the 10% wt.Low GA concentrations (1 and 2.5%) improved hardness with minimal surface changes, while higher levels (7.5 and 10%) significantly enhanced antifungal efficacy but compromised roughness and aesthetics. A 5% GA concentration offered a balanced compromise, necessitating further investigation.
Keywords: polymethyl methacrylate; denture base; gum Acacia arabica; antifungal agents; surface properties; Candida albicans